MAIN CRITERIA AND METHOD OF DETECTION OF UNDERGROUND WATER BY ELECTRICAL PROSPECTING (Proceedings of the YSU C: Geological and Geographical Sciences, 2019)
Under the regularities of formation of groundwater, we understand the steady spatial, temporal and genetic relationships of groundwater with the geological and hydrogeological conditions and natural-territorial complexes of the region. As water-control criteria, increased fracturing, it's mainstream, lithological, geomorphological, geobotanical and other features should be noted. The presence of the above criteria allows you to identify promising areas for targeted field research. The presence of the above mentioned criteria allows to identify promising areas for targeted field research. Among these methods, one of the main ones we recommend is geophysical, which are successfully used in the search for groundwater in a number of volcanic areas.
Keywords: underground water; aquifer; water control criteria; watercourse; geophysical methods; springs; graphs of $ρ_k$; electrical profiling $ΔU$